Pelatihan STEAM (Science, Technology, Engineering, Arts, and Mathematics) bagi Guru Sekolah Dasar - Mohammad Zainudin Aklis (LPPM-IAI Hidayatullah Batam, 2026)
The 21st century requires educational approaches that integrate science, technology, engineering, arts, and mathematics (STEAM) to foster critical thinking, creativity, collaboration, and problem-solving skills from an early educational level. However, the implementation of STEAM in elementary schools remains challenged by teachers’ limited conceptual understanding and the absence of structured and sustainable training models. This article aims to formulate a conceptual framework for STEAM training for elementary school teachers aligned with the Merdeka Curriculum. This community service uses the Participatory Action Research Method, and synthesizing relevant academic literature, educational policies, and empirical studies published between 2021 and 2025. The findings propose a STEAM training model consisting of four main phases: strengthening the philosophical foundation of STEAM, integrating local wisdom and the Merdeka Curriculum, developing project-based STEAM teaching modules, and establishing a collaborative and reflective professional learning community. The model emphasizes that effective STEAM training should not merely focus on technical skills but must be grounded in a strong conceptual foundation to support sustainable teacher professional development. This conceptual framework is expected to serve as a reference for designing adaptive STEAM training programs for elementary school teachers in response to 21st-century learning demands.